The Complicated Relationship of Religious Rituals and Morality: A Critical Review - Al-Razi, Muhammad Fakhruddin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2025)
While many scholarly studies have focused on the relationship between religion and morality, religion encompasses various domains, necessitating a focused examination of religious rituals and their role in human morality. Reviewing research findings and theoretical frameworks, this article explores how rituals influence moral behavior. The investigation yields varying and sometimes contradictory empirical results form various literature, resulting in inconclusive outcomes. However, theoretical models consistently suggest that rituals affect morality through multiple mechanisms: behavioral, spiritual, behavioral-spiritual, social-interactional, and anthropological. The findings indicate that the influence of rituals on moral order and behavior is not straightforward, but instead operates through complex processes, including the performance of rituals, their sacred nature, and symbolic mechanisms that shape individual adherence to societal norms. Future research should therefore pursue interconnective investigations and multi-method approaches that integrate key ritual dimensions –such as sacredness, devotion, symbolic meaning, and social context– to provide a deeper empirical understanding of the mechanisms by which religious rituals contribute to the development of human morality.